STRATEGI PENGELOLAAN DAN PEMBELAJARAN PADA ANAK KESULITAN BELAJAR DENGAN PENDEKATAN KOLABORATIF DI SD INKLUSI - Fenty Ardiyanti; Ines Mutia, Gerry Dova Al Ikhsan; Minsih (STKIP Subang, 2025)
The observation focused on the successful implementation of collaborative learning for students with special needs in inclusive elementary schools. The study highlighted the positive outcomes achieved through the collaboration between special teachers, homeroom teachers, and students with various disabilities. This collaborative approach supported the achievement of learning objectives in classrooms with both mainstream and special needs students, facilitating skills development and application of knowledge through peer learning. Co-teaching allowed educators to share knowledge, skills, and experiences, enhancing support and educational opportunities for students. The ongoing development of teachers' skills through collaborative learning and peer interaction during lessons was emphasized as a key benefit of this approach in providing enhanced support and education for all students.